2014
DOI: 10.1002/ange.201409471
|View full text |Cite
|
Sign up to set email alerts
|

A Highly cis‐Selective and Enantioselective Metal‐Free Hydrogenation of 2,3‐Disubstituted Quinoxalines

Abstract: A wide range of 2,3-disubstituted quinoxalines have been successfully hydrogenated with H 2 using borane catalysts to produce the desired tetrahydroquinoxalines in 80-99 % yields with excellent cis selectivity. Significantly, the asymmetric reaction employing chiral borane catalysts generated by the in situ hydroboration of chiral dienes with HB(C 6 F 5 ) 2 under mild reaction conditions has also been achieved with up to 96 % ee, and represents the first catalytic asymmetric system to furnish optically active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Synthesis and Characterization of Iridium(III) Complex Dye: The dye was synthesized by using a previously reported protocol. 4′-methyl-[2,2′-bipyridine]-4-carbaldehyde [44] and the auxiliary ligand 2-methyl-3phenylquinoxaline (mpq) [45] were synthesized according to literature methods. The iridium(III) dimmer [Ir(mpq) 2 Cl] 2 [46] was synthesized by using the similar method of [Ir(ppy) 2 13 13 C NMR spectra were recorded using a Bruker 500 nuclear magnetic resonance spectrometer using CDCl 3 or CD 3 OD as the deuterated solvent.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis and Characterization of Iridium(III) Complex Dye: The dye was synthesized by using a previously reported protocol. 4′-methyl-[2,2′-bipyridine]-4-carbaldehyde [44] and the auxiliary ligand 2-methyl-3phenylquinoxaline (mpq) [45] were synthesized according to literature methods. The iridium(III) dimmer [Ir(mpq) 2 Cl] 2 [46] was synthesized by using the similar method of [Ir(ppy) 2 13 13 C NMR spectra were recorded using a Bruker 500 nuclear magnetic resonance spectrometer using CDCl 3 or CD 3 OD as the deuterated solvent.…”
Section: Methodsmentioning
confidence: 99%
“…[11] These catalysts are highly effective and selective in asymmetric imine hydrogenations.W eattempted to use them for the hydrogenation of 2-methylquinoline,aless bulky substrate that was not studied by either Repo [8] or Du. [9,10] Disappointingly,w eo bserved no reaction (Scheme 1a). We hypothesized that our catalysts were not sterically hindered enough to prevent the coordination of this quinoline to the boron center.T oi ncrease the steric bulk, we intended to change the fused bicyclic structure to as piro-bicyclic structure because the latter consists of two perpendicular rings,w hich produce as teric environment similar to that in Scheme 1.…”
mentioning
confidence: 99%
“…Interestingly, Du and coworkers found that using catalytic amount of B(C 6 F 5 ) 3 (10 mol%) or B( p ‐HC 6 F 4 ) 3 (5 mol%) as a catalyst, the hydrogenation of 2,3‐disubstituted quinoxalines proceeded smoothly to afford a variety of tetrahydroquinoxalines in 80%—99% yields with excellent cis ‐selectivity. Significantly, the asymmetric reaction employing chiral borane catalyst generated by the in situ hydroboration of chiral diene 15b with HB(C 6 F 5 ) 2 has been successfully achieved to give the desired product in high yields with high levels of cis ‐selectivities and enantioselectivities (Scheme ) . However, 2,3‐dialkyl‐ or diarylquinoxalines stayed inert for this catalytic asymmetric reaction.…”
Section: Chiral Boranes Synthesized Via In Situ Hydroborationmentioning
confidence: 99%